Selection of desulfurizing agents and optimization of operational variables in hot metal desulfurization - Silva, Sidiney Nascimento; Vernilli, Fernando; Justus, Sergio Murilo [UNESP]; Araújo, Cláudio Márcio Dos Santos; Longo, Elson [UNESP]; Varela, José Arana [UNESP]; Lopes, José Milton Gabriel; Vidal de Almeida, Bruno (Wiley, 2013)
The growing demand for steels with tighter compositional specifications led the Companhia Siderúrgica Nacional (CSN) to develop more efficient processes. To solve this problem this paper aims to identify the operational variables more impacting in the desulfurization process, specifically in torpedo car, as well as its causes and solutions. Then select and test, with laboratorial and industrial tests, desulfurizing agents based of CaC 2, CaO, CaCO3, and Mg to assess the cost per quantity of product desulfurized. The mixture with best results was not that one with highest content of CaC2. It is believed that this mixture showed better efficiency because of the increased agitation of the bath, produced by the releasing of gas from compound CaCO3 present in this mixture. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: desulfurization; desulfurizing agent; hot metal; De-sulfurization process; Desulfurizing agents; Efficient process; Growing demand; Hot metal; Hot metal desulfurization; Industrial tests; Operational variables; Torpedo car; Calcium carbide; Calcium carbonate; Mixtures; Desulfurization